Case report: Structural brain abnormalities in TUBA1A-tubulinopathies: a narrative review - Pavone, Piero; Striano, Pasquale; Cacciaguerra, Giovanni; Marino, Simona Domenica; Parano, Enrico; Pappalardo, Xena Giada; Falsaperla, Raffaele; Ruggieri, Martino (Frontiers in Pediatrics, 2023)
Introduction Tubulin genes have been related to severe neurological complications and the term “tubulinopathy” now refers to a heterogeneous group of disorders involving an extensive family of tubulin genes with TUBA1A being the most common. A review was carried out on the complex and severe brain abnormalities associated with this genetic anomaly. Methods A literature review of the cases of TUBA1A-tubulopathy was performed to investigate the molecular findings linked with cerebral anomalies and to describe the clinical and neuroradiological features related to this genetic disorder. Results Clinical manifestations of TUBA1A-tubulinopathy patients are heterogeneous and severe ranging from craniofacial dysmorphism, notable developmental delay, and intellectual delay to early-onset seizures, neuroradiologically associated with complex abnormalities. TUBA1A-tubulinopathy may display various and complex cortical and subcortical malformations. Discussion A range of clinical manifestations related to different cerebral structures involved may be observed in patients with TUBA1A-tubulinopathy. Genotype–phenotype correlations are discussed here. Individuals with cortical and subcortical anomalies should be screened also for pathogenic variants in TUBA1A.